ANALISIS SISTEM PEMELIHARAAN INFANT WARMER DI LABORATORIUM TERPADU - Robertus Robin Saputra Manao; Salomo Sijabat (JURNAL MUTIARA ELEKTROMEDIK, 2020)
Medical devices are devices that are always in a ready to use condition and can function properly. This requires the Sari Mutiara University Integrated Laboratory to assist and medical equipment as effectively and efficiently as possible. This study aims to look at the Infant warmer monitoring system in the USM-Indonesia Integrated Lab.This research is a descriptive analysis with qualitative methods. Theinstrument used is by conducting in-depth interviews, observation and documents.The results of this study indicate that in its implementation, the maintenance system cannot be run properly, due to limited technical personnel, lack of training, insufficient maintenance costs, maintenance SOPs are not in accordance with procedures. Planning, organizing, and monitoring are not well implemented so that the preventive and corrective maintenance systems cannot run properly.